Hydrolysis of a Lipid Membrane by Single Enzyme Molecules: Accurate Determination of Kinetic Parameters1. Issue 3 (27th November 2014) - Rabe, Michael; Tabaei, Seyed R.; Zetterberg, Henrik; Zhdanov, Vladimir P.; Höök, Fredrik
Abstract The accurate determination of the maximum turnover number and Michaelis constant for membrane enzymes remains challenging. Here, this problem has been solved by observing in parallel the hydrolysis of thousands of individual fluorescently labeled immobilized liposomes each processed by a single phospholipase A2 molecule. The release of the reaction product was tracked using total internal reflection fluorescence microscopy. A statistical analysis of the hydrolysis kinetics was shown to provide the Michaelis–Menten parameters with an accuracy better than 20 % without variation of the initial substrate concentration. The combined single‐liposome and single‐enzyme mode of operation made it also possible to unravel a significant nanoscale dependence of these parameters on membrane curvature.